CHANGES IN THE GASTROINTESTINAL TRACT IN THE TREATMENT OF GLUCOCORTICOSTEROIDS USED IN CHILDREN WITH NEPHROTIC SYNDROME: RESULTS OF A RETROSPECTIVE STUDY (World Bulletin of Public Health, 2022)
In the last decade there has been a sharp increase in chronic kidney diseases (CKD) among children. In the US, Europe, Australia, Asian countries, it is noted that one-tenth of the world's population suffers from a violation of kidney function. In 50% of patients with SBK, the disease is detected at the 3-5 stage of chronic renal failure (CRF), in 10% of patients at the terminal stage.At present, insufficient research has been conducted in the country to study the features and complications of kidney disease in children. (Umarov R.Kh. 2010; Sharipov A.M. 2012; Khamzaev K.A., 2019; Rakhmonova L.K. 2020; Karimova U.N. 2020;)